2014
DOI: 10.1002/aenm.201400816
|View full text |Cite
|
Sign up to set email alerts
|

Interface Design to Improve the Performance and Stability of Solution‐Processed Small‐Molecule Conventional Solar Cells

Abstract: A systematic study on the effect of various cathode buffer layers on the performance and stability of solution-processed small-molecule organic solar cells (SMOSCs) based on tris{4-[5-(1,1-dicyanobut-1-en-2-yl)-2,2-bithiophen-5-yl]phenyl}amine (N(Ph-2T-DCN-Et) 3 ):6,6-phenyl-C71-butyric acid methyl ester (N(Ph-2T-DCN-Et) 3 :PC 70 BM) is presented. The power conversion effi ciency (PCE) in these systems can be signifi cantly improved from approximately 4% to 5.16% by inserting a metal oxide (ZnO) layer between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 43 publications
2
71
0
Order By: Relevance
“…In the first version of this p-i-n structure, the metal contacts (Al, Ag or Au) were directly evaporated onto the PCBM layer [16,18]. However, as demonstrated in organic solar cells, such a PCBM/metal contact is not optimized for electron extraction due to the energy level mismatch [21,22]. Therefore, interface engineering has been carried out between the PCBM and metal contact by inserting additional layers, such as thermally evaporated LiF [13], Ca [23], and C 60 /bathocuproine (BCP) [15], or solution processed poly[(9,9-bi s(30-(N,N-dimethylamino)propyl)-2,7-fluorene)-alt-2,7-(9,9-dioct ylfluorene)] (PFN) [24], Bis-C 60 surfactant [17], TiO x [25], ZnO [26] etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the first version of this p-i-n structure, the metal contacts (Al, Ag or Au) were directly evaporated onto the PCBM layer [16,18]. However, as demonstrated in organic solar cells, such a PCBM/metal contact is not optimized for electron extraction due to the energy level mismatch [21,22]. Therefore, interface engineering has been carried out between the PCBM and metal contact by inserting additional layers, such as thermally evaporated LiF [13], Ca [23], and C 60 /bathocuproine (BCP) [15], or solution processed poly[(9,9-bi s(30-(N,N-dimethylamino)propyl)-2,7-fluorene)-alt-2,7-(9,9-dioct ylfluorene)] (PFN) [24], Bis-C 60 surfactant [17], TiO x [25], ZnO [26] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the stability of the ZnO/Al based device is still quite poor owing to the instable Al cathode. 23 In the previous studies we have already demonstrated DMAPA-C 60 as a promising interlayer being compatible to a Ag cathode. 23 Here we introduced a new interfacial layer (PDINO) to modify the stable Ag cathode for expanding the currently rather limited choice of available electron transporting layers (ETLs) for small molecule OSCs (see Fig.…”
Section: à2mentioning
confidence: 99%
“…23 However, as compared to its polymeric counterparts, the development of interface layers applied in small molecule systems has largely been overlooked until recently. Therefore, the development of stable and effective device architectures based on interfacial engineering should be also highlighted in the photovoltaic optimization of SMOSCs.…”
Section: 22mentioning
confidence: 99%
“…[16,[29][30][31][32][33] Despite tremendous efforts have been made to enhance the stability of OSCs based on the consideration of extrinsic factors like reactions with oxygen and interface degradation, [3,16,24,[34][35][36] intrinsic reactions were less frequently reported due to the complexity of separating intrinsic versus extrinsic effects. [30,37] An important intrinsic mechanism is thermal degradation because an optimal BHJ morphology was frequently found to be a metastable state which readily moves toward a less efficient thermodynamic equilibrium state.…”
mentioning
confidence: 98%